On the Issue of the Effectiveness of the Department for Registration of Medicines - A. V. Foteeva; N. A. Koneva; N. B. Rostova (Разработка и регистрация лекарственных средств)
Introduction. New requirements for the registration of generic drugs after the entry of the Russian Federation into the Eurasian Economic Union (EAEU) and the signing of the Agreement on Common Principles and Rules for the Circulation of Medicinal Products identified a number of problems and opportunities that specialists in drug registration and working with regulatory authorities. The presented prospects for drug registration predetermine the list of tasks for the reorganization of the work of the department for work with regulatory authorities and the need to improve the competence of the employees of the manufacturers in order to carry out effective work.Aim. Assessing critical steps in the generic drug registration process to improve the efficiency and organization of the Regulatory Affairs department.Materials and methods. The materials of the study were available publications in peer-reviewed journals on thematic queries compiled according to the keywords of the chosen subject, official websites, regulatory legal acts regulating the procedure for registering drugs in the Russian Federation, the EAEU and foreign countries.Results and discussion. A brief overview of regulatory issues on drug registration according to the requirements of the Eurasian Economic Union is presented. The critical stages of the drug registration process and the tasks that need to be solved in order to ensure the effective work of the department for working with regulatory authorities in the implementation of drug registration processes in the Russian Federation, the EAEU and other countries were identified. The role of professional qualifications of specialists involved in the preparation of the registration dossier and the processes of registration of medicines is indicated.Conclusion. Changes in the legal regulation of the registration process and the imperfection of the requirements for specialists who carry out the procedures for preparing the registration dossier determine the need to develop organizational technologies and measures at the organization level aimed at standardizing all processes and forming professional specialized competencies of personnel.